2019
DOI: 10.1177/0276236619889553
|View full text |Cite
|
Sign up to set email alerts
|

Are Negative Attitudes Toward Dreams Just the Inverse of Positive Attitudes Toward Dreams? An Empirical Investigation

Abstract: As dreaming is a universal phenomenon, it seems natural that everyone has a more or less explicitly defined attitude toward dreams. Recent studies indicate that positive and negative attitude toward dream scales—even given there is considerable overlap—might not be related to the same variables. The findings of the present online survey ( N = 2,056) using 22 attitude items indicated that positive and negative attitudes can be differentiated through confirmatory factor analysis and that variables like age, educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 13 publications
(29 reference statements)
3
3
1
Order By: Relevance
“…Similar to previous studies (Bulkeley & Schredl, 2019; Schredl, 2013; Schredl et al, 2020), the findings indicated the variability of the attitude towards dreams dimension: Whereas 30% to 50% of this sample indicated a positive attitude towards dreams, about 20% to 35% were not that positive about dreams (see Table 2). As mentioned above, this ratio might be slightly biased, as one would expect somewhat lower percentages of persons with positive attitudes towards dream in representative sample as their average dream recall frequency in the general population is lower.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Similar to previous studies (Bulkeley & Schredl, 2019; Schredl, 2013; Schredl et al, 2020), the findings indicated the variability of the attitude towards dreams dimension: Whereas 30% to 50% of this sample indicated a positive attitude towards dreams, about 20% to 35% were not that positive about dreams (see Table 2). As mentioned above, this ratio might be slightly biased, as one would expect somewhat lower percentages of persons with positive attitudes towards dream in representative sample as their average dream recall frequency in the general population is lower.…”
Section: Discussionsupporting
confidence: 90%
“…This might be explained by a gender specific dream socialization as girls talk more about dreams with peers than boys (Schredl et al, 2015). Similar, these large-scaled studies (Bulkeley & Schredl, 2019; Schredl, 2013, 2020; Schredl et al, 2014b) showed a small but significant decrease of positive attitudes towards dreams with age. As the attitude towards dreams score was quite stable over a 5-year period (Schredl et al, 2019), one might speculate that the age differences might be explained by cohort effects, that is, the attitude towards dreams differs between the generations.…”
supporting
confidence: 55%
See 3 more Smart Citations